2007
DOI: 10.1111/j.1467-8276.2007.00965.x
|View full text |Cite
|
Sign up to set email alerts
|

The Pricing of Experience Goods: The Example ofen primeurWine

Abstract: The market for "primeur" wine in the Bordeaux region allows producers to sell wine that is still in barrels. As with all experience goods, producers send quality signals to uninformed buyers. Using original data on Bordeaux wines, we show that the pricing behaviour of producers depends to a large extent on their reputation, and much less on short-term changes in quality (as measured by experts' grades). We also find that the primeur price has an informative role, since a 10 percent increase in primeur price le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(42 citation statements)
references
References 33 publications
0
39
0
3
Order By: Relevance
“…While it is recognized that there is heterogeneity in individual consumers' behavior and their valuations of wines, this study showed that decisive decisions were made by consumers regarding their choices of Champagnes when brand and label information were disclosed. Labeling schemes in European wine countries, unlike New World wine countries, have been emphasized in promotion to strengthen the reputation effects of wine quality with the place of origin emphasized to mitigate market failure (Bougherara and Grolleau 2005; Ali and Nauges 2007).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…While it is recognized that there is heterogeneity in individual consumers' behavior and their valuations of wines, this study showed that decisive decisions were made by consumers regarding their choices of Champagnes when brand and label information were disclosed. Labeling schemes in European wine countries, unlike New World wine countries, have been emphasized in promotion to strengthen the reputation effects of wine quality with the place of origin emphasized to mitigate market failure (Bougherara and Grolleau 2005; Ali and Nauges 2007).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Examples can be found in wine market studies by Loureiro (2003), Landon and Smith (1997), Lecocq & Visser (2006), Perrouty et al (2006), Ali and Nauges (2007); in the meat markets examined by Roosen et al (2003), Alfnes (2004), Loureiro & McCluskey (2000); as well as in the market for Mediterranean products such as oranges, grapes and olive oil as described by Scarpa, Philippidis & Spalatro (2005), and again for olive oil as reported by Van der Lans et al (2001) and Scarpa and Del Giudice (2004). 4 General reviews of this issue can be found in Skuras and Dimara (2004) and van Ittersum et al (2007).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, all of the problematic unobservable characteristics are most likely at the winery level and constant within the observed timeframe; they will be controlled for by including a winery-level fixed effect, u j . 4 Previous work has made similar assumptions pertaining to the consistency of these winery-level unobservable variables across time (Ali and Nauges 2007;Delmas and Grant 2010;Haeger and Storchmann 2006). ε ij likely contains shocks such as favorable or unfavorable weather for that particular wine's growing season, natural variation in the outcome resulting from the winemaking process, and other individual wine-specific shocks, which will be independent of the observed independent variables.…”
Section: Methodsmentioning
confidence: 99%